Revision of the species Grouvellinus Champion, 1923 (Coleoptera: Elmidae) with long median pronotal carina, including descriptions of four new species from China - Bian, Dongju; Jäch, Manfred A. (Zootaxa, 2019)
Four new species of Grouvellinus Champion, 1923 with very long median pronotal carina are described from China: G. hongkongensis sp. nov. (Guangdong, Guangxi, Hong Kong), G. longiusculus sp. nov. (Jiangxi), G. mediocarinatus sp. nov. (Fujian, Guangdong), and G. robustus sp. nov. (Anhui). These species are obviously closely related to G. bishopi Jäch, 1984 described from Malaysia (Selangor). The latter is here recorded for the first time from Kedah and Perak (Malaysia). Habitus photographs, detailed line drawings of the male genitalia, as well as a key to the males of the species of Grouvellinus with very long median pronotal carina are provided.